Sexual behavior in a cohort of patient affected by fibromyalgia and/or vulvodynia - Anna Ghizzani; Teresa Pozzi; Gloria Bocci (Publiediting, 2015)
Fibromyalgia, characterized by widespread musculoskeletal pain, negatively impacts sexuality by provoking dispareunia, and loss of desire and of dyadic gratification. Chronic pain syndromes tend to associate and FM women have a higher probability to develop vulvodynia than women not affected by fibromyalgia. Vulvodynia, characterized by burning pain that interferes with sexual penetration, is classified as Genitopelvic/Penetration Disorders in DSM 5. The association between Fibromyalgia and vulvodynia is difficult to recognize because patients tend to attribute all symptoms to disease spread and not think that dyspareunia may have different origins. To establish the necessary criteria for the differential diagnosis between the two syndromes, we evaluated the characteristics of dyspareunia and sexual behavior of fibromyalgia patients versus vulvodynia patients and we found significant differences on the onset of burning pain, orgasmic capability, and sexual frequency.